Dynamic Knee Joint Stiffness and Contralateral Knee Joint Loading during Prolonged Walking in Patients with Unilateral Knee Osteoarthritis - Gustafson, Jonathan A. (Gait Posture, 2018)
BACKGROUND: Long duration walking, a commonly recommended treatment option for knee osteoarthritis (OA), may lead to increased knee joint loading. RESEARCH QUESTION: To evaluate the effects of prolonged walking on dynamic knee joint stiffness and contralateral knee joint contact forces (KCFs) in individuals with unilateral symptomatic knee OA. METHODS: Twenty-six older adults with knee OA completed a 45-minute bout of walking on a treadmill. Dynamic knee joint stiffness, estimated KCFs, measured ground reaction forces (GRFs), and simulated muscle forces were evaluated for both the symptomatic and asymptomatic limbs at 15-minute intervals using repeated measures, analysis of variance (ANOVA). RESULTS: Dynamic knee joint stiffness during the early weight-acceptance phase of gait was significantly higher for the symptomatic limb throughout the 45-minute bout of walking. A significant increase in peak KCFs and simulated muscle forces were also observed during the weight-acceptance phase of gait for both limbs after 30 and 45 minutes of walking. Additionally, significantly elevated peak KCFs and muscle forces were observed during the late-stance phase of gait for the contralateral asymptomatic limb throughout the 45-minute bout of walking. SIGNIFICANCE: Walking durations of 30 minutes or greater lead to increased knee joint loading. Additionally, the elevated dynamic knee joint stiffness observed for the symptomatic knee during the weight acceptance phase of gait appears to be unrelated to the knee joint loading profile. Finally, the greater KCFs during the late-stance phase of gait observed for the asymptomatic limb are consistent with previously demonstrated risk factors for OA development and progression.